2015
DOI: 10.1128/mcb.00665-15
|View full text |Cite
|
Sign up to set email alerts
|

Lysine Acetylation of CREBH Regulates Fasting-Induced Hepatic Lipid Metabolism

Abstract: dCyclic AMP-responsive element-binding protein 3-like 3, hepatocyte specific (CREBH), is a hepatic transcription factor that functions as a key regulator of energy homeostasis. Here, we defined a regulatory CREBH posttranslational modification process, namely, lysine-specific acetylation, and its functional involvement in fasting-induced hepatic lipid metabolism. Fasting induces CREBH acetylation in mouse livers in a time-dependent manner, and this event is critical for CREBH transcriptional activity in regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 27 publications
2
41
0
Order By: Relevance
“…Previously, we demonstrated that acetylation of CREBH at the lysine residue K294 is critical for CREBH-PPAR␣ interaction and optimized CREBH transcriptional activity in lipid metabolism in response to fasting (14). As shown in Fig.…”
Section: Resultsmentioning
confidence: 76%
See 3 more Smart Citations
“…Previously, we demonstrated that acetylation of CREBH at the lysine residue K294 is critical for CREBH-PPAR␣ interaction and optimized CREBH transcriptional activity in lipid metabolism in response to fasting (14). As shown in Fig.…”
Section: Resultsmentioning
confidence: 76%
“…5). As we demonstrated previously, CREBH is also required in order to maintain lipid homeostasis by regulating lipolysis and fatty acid oxidation during the daytime or upon fasting (7,10,14). Apparently, CREBH functions as a major transcriptional activator that drives the processes of lipid and glucose mobilization in response to energy demands.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Fasting and glucagon increases CREBH acetylation, which is required for the formation of the CREBH-PPARα transcriptional complex [49]. In addition to regulating each other's transcription in fasted liver [47], CREBH and PPARα synergize to activate FGF21 gene expression through the binding of the CREBH-PPARα complex to a highly conserved CRE-peroxisome proliferator-activated response element (PPRE) site in the FGF21 proximal promoter [50].…”
Section: Regulation By Hormones Glucagon and Insulinmentioning
confidence: 99%